MC4-R variant confirms its association with obesity during progression from childhood to adolescence - Angelika Mohn; Armando Di Ludovico; Nella Polidori; Cosimo Giannini; Giada Di Pietro; Federico Lauriola; Francesco Chiarelli (Scientific Reports)
Abstract The rs12970134 variant near the melanocortin receptor 4 (MC4-R) has gained relevance suggesting an age dependent phenotypic effect in the induction of obesity in young age. A previous study evaluating 740 Caucasian children has shown this association in prepubertal children older than 8 years. The aim of this study was to assess whether the obesogenic effect of M4CR gene contributed to obesity also in adolescence. After 8 years participants of the original study were contacted and invited to perform an anthropometric evaluation. Out of 35 carriers of the AA risk allele of MC4-R, 12 subjects accepted to participate. Adolescent subjects with the AA risk allele of MC4-R were matched with 24 and 48 subjects, respectively for AG and GG variants. Differences between the three MC4-R genotypes for anthropometric data, for percentage of overweight and obesity and for changes in BMI-SDS over visit have been assessed. At Visit 1 (baseline examination study), the AA risk genotype was confirmed to be associated with higher BMI-SDS (1.3 ± 0.4 vs 0.4 ± 0.1) and waist circumference (66.5 ± 5.8 vs 60.9 ± 7.1) when compared to the GG genotype (p < 0.016 both). At Visit 2 the AA genotype not only was associated with a higher BMI-SDS (1.07 ± 0.5 vs 0.02 ± 0.8) and WC (95.6 ± 13.3 vs 64.9 ± 13.5) when compared to GG genotype, but also when compared to AG genotype (vs 0.5 ± 0.1 and 62.9 ± 10.0, p < 0.016). Whereas AA genotype demonstrated no change of BMI-SDS between visit 1 and visit 2 (p00.32), AG and GG genotype showed a significant reduction (p = 0.01 and 0.001 respectively). Furthermore, a higher percentage of patients were affected by overweight/obesity in the AA genotype compared to AG and GG genotypes (50% vs 20.8% vs 16.5% p = 0.03). This study demonstrates that the rs12970134 variant not only exerts an obesogenic influence in the prepubertal age but remains a major risk factor also during adolescence.